2020
DOI: 10.1093/gerona/glaa145
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cumulative Anticholinergic Use on the Cognitive Function of Older Adults: Results from the Personality and Total Health (PATH) Through Life Study

Abstract: Abstract Background Multiple comorbidities are common in older adults, resulting in polypharmacy that often includes medications with anticholinergic properties. These medications have multiple side effects, which are more pronounced in the older population. This study examined the association between the use of anticholinergics and changes in the cognitive function of older adults. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…However, anticholinergic medication, as quantified by the Anticholinergic Drug Scale or the Anticholinergic Risk Scale was significantly associated with major preexisting NCD [12 ▪▪ ]. This confirms recent findings that long-term intake of anticholinergics is associated with poorer cognitive and physical functioning in a general, nonsurgical, population [14,15].…”
Section: Medicationsupporting
confidence: 85%
“…However, anticholinergic medication, as quantified by the Anticholinergic Drug Scale or the Anticholinergic Risk Scale was significantly associated with major preexisting NCD [12 ▪▪ ]. This confirms recent findings that long-term intake of anticholinergics is associated with poorer cognitive and physical functioning in a general, nonsurgical, population [14,15].…”
Section: Medicationsupporting
confidence: 85%
“…The levels of LTCI certification have been shown to be highly correlated with the Barthel Index (Spearman’s ρ= −0.86) and moderately correlated with Mini-Mental State Examination (MMSE) scores (Spearman’s ρ= −0.42) [ 20 ]. We defined functional disability as the onset of long-term care needs at support level 1 or above [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…When measured this way, studies of AChB and cognitive ability often produce discordant results 16 . There are reports of positive associations between anticholinergic use and executive function 12,[18][19][20][21] , associative learning 22 , visual- 23 , episodic- 24,25 , and short-term memory 26 , delayed and immediate recall 27 , language abilities 28 , visuospatial skills 28 , attention 28 , and reaction time 28 . However, some authors have found no evidence for delayed and immediate recall 21,22,28,29 , reaction time 22 , executive function 23,27 , language abilities 27,29 , working memory 25,27 , processing speed 25 , and implicit- 28 and semantic 25 memory.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports of positive associations between anticholinergic use and executive function 12,[18][19][20][21] , associative learning 22 , visual- 23 , episodic- 24,25 , and short-term memory 26 , delayed and immediate recall 27 , language abilities 28 , visuospatial skills 28 , attention 28 , and reaction time 28 . However, some authors have found no evidence for delayed and immediate recall 21,22,28,29 , reaction time 22 , executive function 23,27 , language abilities 27,29 , working memory 25,27 , processing speed 25 , and implicit- 28 and semantic 25 memory. Additionally, because anticholinergic scales sometimes include different drugs and score the same drugs differently, they could represent another source of variation in reported findings.…”
Section: Introductionmentioning
confidence: 99%